CDMA2000 physical layer simulation for 3G mobile systems / Norfariza Kamaruddin - Kamaruddin, Norfariza (2003)
Success of wireless services and desire for higher rate wireless services, improved spectrum efficiency were a major design goal in the elaboration of CDMA2000. CDMA2000 offers a seamless and evolutionary high data rate upgrade path for current users of2G and 2.5G CDMA technology. This project describes the simulation of CDMA2000 physical layer forward link system. The simulation is specified for Forward Fundamental Channel (F-FCH) of CDMA2000 1XRTT system. The simulation model is designed and simulated following the standard that being specified by the 3G Partnership Project 2 (3GPP2). The simulation is implemented using the Matlab and Simulink software provided by Mathworks Co. The purpose of this project is to study the performance of the simulation model in different data rate specified for CDMA2000 with Radio Configuration 3, the performance of channel coding, interference and other parameters. The model developed may be a very valuable tool for investigating the CDMA200 for 3G mobile system development.